The Impact of Imagery Rescripting and Reprocessing Therapy on Emotional Processing in Women with Multiple Sclerosis - Dizaj Khalili , Mahtab; Makvand Hosseini, Shahrokh; Sabahi , Parviz (Advances in Nursing & Midwifery, 2023)
Introduction: Multiple sclerosis (MS) is a chronic disease that affects the central nervous system and causes numerous psychological issues in patients. The present study aimed to investigate the effect of imagery rescripting and reprocessing therapy (IRRT) on emotional processing in women with MS. Methods: This was a quasi-experimental, pretest-posttest study with two groups (intervention and control). The statistical population comprised MS-afflicted women registered with the Tehran MS Association. Thirty women with MS were selected via convenience sampling and were placed into experimental and control groups (n=15). The intervention group received seven 90-minute sessions of imagery rescripting and reprocessing therapy, whereas the control group received no educational intervention during this period. The Emotional Processing Scale was used to collect data, and the Repeated measures ANOVA procedure was used for data analysis. Results: As regards emotional processing, there was a significant difference between the IRRT group and the control group (P<0.001). The results demonstrated that imagery rescripting and reprocessing improved emotional processing in MS patients, whereas the control group exhibited no significant change over time. Conclusions: IRRT assists individuals in managing negative emotions. Therefore, imagery rescripting and reprocessing training is recommended to improve emotional processing in MS patients.